Toward a modular and efficient distribution for Web service handlers. (19th June 2012) - Yildiz, Beytullah; Fox, Geoffrey C.
SUMMARY: Over the last few decades, distributed systems have architecturally evolved. One recent evolutionary step is SOA. The SOA model is perfectly engendered in Web services, which provide software platforms for building applications as services. Web services utilize supportive capabilities such as security, reliability, and monitoring. These capabilities are typically provisioned as handlers, which incrementally add new features. Even though handlers are very important, the method of utilization is crucial for obtaining potential benefits. Every attempt to support a service with an additional handler increases the chance of an overwhelmingly crowded handler chain. Moreover, a handler may become a bottleneck because of its comparably higher processing time. In this paper, we present the Distributed Handler Architecture to provide an efficient, scalable, and modular architecture. The performance and scalability benchmarks show that the distributed and parallel handler executions are very promising for suitable handler configurations. The paper is concluded with remarks on the fundamentals of a promising computing environment for Web service handlers. Copyright © 2012 John Wiley & Sons, Ltd.